Purification of Recombinent p19ARF: Protein Interaction and Stability Analysis - Liu, Xin; Fang Du, Lin; He Huang, Xin; Yan Zhu, De; Li, Jia; Zhang Wang, Jing (Asian Journal of Chemistry, 2010)
The protein alternate reading frame (ARF) known as p19ARF in mice is unique in its capacity to facilitate cancer suppression. Here, we report that recombinent 10His-p19ARF expressed in Escherichia coli BL21 (DE3) could be purified under native condition by nickel chelating affinity chromatography and have functional structure. 0.3 mg 10His-p19ARF per liter culture could be obtained after the purification process. This recombinant protein was recognized by western blot with anti-His antibody. Then GST pull-down assay revealed its interaction with TAp63γ (a member of the p53 family) in vitro. By describing its temperature and pH dependent stabilities using fluorescence measurements, the surface environment of the C-terminal region of 10His-p19ARF was especially found to be hydrophobic. The 10His-p19ARF unfolding with heat was a two-state mechanism. A significant change of tryptophan fluorescence of p19ARF upon β-mercaptoethanol suggested its disulfide bond-dependent conformation